2020
DOI: 10.1192/j.eurpsy.2020.110
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory certification for clozapine prescribing

Abstract: The Clozapine Prescription Rates and Current Clinical Practice Clozapine is the only registered treatment for therapy-resistant schizophrenia (meaning, after treatment with two other antipsychotics failed or were not tolerated), psychosis in Parkinson's disease, and, in the United States, for suicidality. Off-label, clozapine is prescribed for therapyresistant disorders, especially therapy-resistant bipolar, borderline personality, violent behavior, or self-harm in patients with psychosis, aggressive behavior,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“… 34 , 47 Recently, a mandatory training program for prescribers, which aims to improve the knowledge about clozapine prescription was proposed in order to overcome these issues. 48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 34 , 47 Recently, a mandatory training program for prescribers, which aims to improve the knowledge about clozapine prescription was proposed in order to overcome these issues. 48 …”
Section: Discussionmentioning
confidence: 99%
“…34,46 Multiple recent studies have shown and confirmed the earlier finding by Tiihonen 34,47 Recently, a mandatory training program for prescribers, which aims to improve the knowledge about clozapine prescription was proposed in order to overcome these issues. 48 Here, we outline our proposed modifications of the national Serbian guidelines. Based on the international literature and the responses we obtained from this survey, we propose three modifications.…”
Section: Major Obstacles For Prescribing Clozapinementioning
confidence: 99%
“…Clozapine underutilization appears to be attributable particularly to clinician's concerns regarding potential side-effects, especially an overestimation of the risks associated with blood dyscrasia 49*,52,54,55 and a lack of resources for blood sampling and other monitoring procedures 52 . Clinician's apprehension appears to be further amplified by limited knowledge regarding treatment algorithms and side effect management 52,54,56,57 . Importantly, this might result in a vicious cycle of less prescription leading to less expertise 57 .…”
Section: Attitude Of Psychiatrists Towards Clozapinementioning
confidence: 99%
“…Clinician's apprehension appears to be further amplified by limited knowledge regarding treatment algorithms and side effect management 52,54,56,57 . Importantly, this might result in a vicious cycle of less prescription leading to less expertise 57 . Furthermore, psychiatrists predominantly presume that patients would not accept clozapine and its monitoring requirements 53* , regard clozapine treatment as a burden for both patients and prescribers 58,59** , and assume that patients receiving clozapine are less satisfied 60 .…”
Section: Attitude Of Psychiatrists Towards Clozapinementioning
confidence: 99%
“…The mental health pharmacist also has an important role here. The suggestion that education and training in the use of clozapine must become a mandatory requirement of all psychiatry residence and continuing professional development programmes 32 would need to take into account the fact that prevention of CIGH requires a concerted effort from all those involved in the care of the patient, not just the prescribing psychiatrist.…”
Section: Prevention Of Cighmentioning
confidence: 99%